ROLE OF TEACHERS IN THE IMPLEMENTATION OF ONLINE LEARNING DURING THE CORONA VYRUS PANDEMIC BETWEEN MTS ASY-SYAFI’IYYAH AND MTS MIFTAHUL JANNAH - Prasetiyo, Agung; Mufidah, Nuril; Nihayaturrohmah, Firda (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
The development of science in the field of technology has a huge impact, especially in the field of education. In the era of the industrial revolution 4.0, it is required to be able to master technology, such as the internet. Then, the role of strengthening the character of teachers in technological development is also very important, especially when this pandemic demands online learning. The majority of teachers who are not in urban areas or the non-favorite school category still do not have the skills to apply online learning media, mainly due to age. Therefore, student responses also vary to the learning that is being carried out. So that teachers are also required to be responsive to the demands of the times. The role of teachers in the world of modern education must also add complexity. Teachers are not only teachers but must also instill moral character in students, especially the use of technological media such as Whatsapp. In this paper, MTS Asy-Syafi'iyah Trenggalek and MTs Miftahul Jannah Trenggalek are used as a model of how the online learning process during a pandemic.